2023
DOI: 10.1002/hpm.3626
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review to identify the challenges to achieving effective patient flow in public hospitals

Abstract: This systematic review aims to uncover the challenges related to patient flow from a whole public hospital perspective and identify strategies to overcome these challenges. A search in Medline, Emcare and PubMed was conducted and 24 articles published in English, from 2015 to 2020, were selected in relation to patient flow challenges and strategies. Analysis of the articles was completed using a thematic approach to identify common themes in relation to the area of focus. Strategies from the literature were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…This resulted in a successful reduction of waiting times for elective admissions and the ED boarding time and increased hospital operational efficiency. The role of bed management in improving patient flow and hospital operational efficiency has been confirmed in several studies 36 37…”
Section: Discussionmentioning
confidence: 88%
“…This resulted in a successful reduction of waiting times for elective admissions and the ED boarding time and increased hospital operational efficiency. The role of bed management in improving patient flow and hospital operational efficiency has been confirmed in several studies 36 37…”
Section: Discussionmentioning
confidence: 88%
“…This category includes studies on throughput time, patient outcomes, provider satisfaction, older adults' experience in the ED, and ED patient care processes [ 7 , 30 , 32 , 33 , 35 , 36 , 55 , 57 , 59 , 63 74 , 76 , 78 , 79 ]. The third category encompasses studies related to challenges specifically related to patient flow [ 15 , 29 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number of criteria met varied across the reviews, with the minimum being 5 out of 11 [ 60 ] and the maximum being 11 out of 11 [ 57 , 64 , 66 , 68 ]. Among the assessed reviews, one scoping review was determined to be of low quality [ 60 ], nine were categorised as moderate quality [ 13 , 27 , 34 36 , 58 , 73 , 74 , 77 ], and the remaining 27 were deemed high quality [ 7 , 15 , 29 33 , 39 , 43 , 55 57 , 59 , 61 – 69 , 71 , 72 , 75 , 76 , 78 80 ]. Notably, all reviews met criteria 8 and 11, which pertain to the appropriate methods used to combine studies and the recommendations for policy and/or practice supported by the reported data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient flow can be defined as the movement of patients through the entire healthcare facility [1] encompassing arrivals, admissions, and discharges. In an ideal state, a hospital's capacity is perfectly matched to its demand, allowing patients to flow through the system seamlessly [2]. Suboptimal patient flow, on the other hand, can lead to adverse outcomes for patients and organisational inefficiency.…”
Section: Introductionmentioning
confidence: 99%